Serum eosinophilic cationic protein: A marker of eosinophilic infiltration in inflammatory bowel disease? - Gülen ARSLAN; Mehmet CİNDORUK; Gül B. Ülkar; İ. Safa YILDIRIM (Turkish Journal of Gastroenterology, 2019)
-